Soils & Fertilizers for Master Gardeners: The Florida Gardener's Guide to Landscape Fertilizers - Amy L. Shober (EDIS, 2008)
SL-266, a 4-page illustrated fact sheet by Amy L. Shober, provides information about fertilizers and associated fertilizer terminology to help consumers make educated decisions when purchasing fertilizers and using them in the home landscape or garden. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Published by the UF Department of Soil and Water Science, August 2008.